Molybdenum-copper superfine composite powder and preparation method thereof
Molybdenum copper ultrafine composite powder is prepared by liquid phase mixing and atomization treatment, combined with hydrogen gradient thermal reduction and ultrasonic vibration screening, which solves the composition segregation and density difference of molybdenum copper alloys in the prior art, and realizes the Molybdenum copper material with high density and excellent thermoelectric properties.
Patent Information
- Application Number
- CN202411648355.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art has problems such as component segregation, tissue holes, and density differences in the preparation of molybdenum copper alloys, making it difficult to achieve mass production. In addition, mechanical alloying methods are prone to introduce impurities, reducing the thermal and electrical properties of the materials.
The liquid phase of molybdenum copper is fully mixed, and the aqueous prealloy molybdenum powder is obtained by aerosolization or water atomization treatment. The hydrogen gradient thermal reduction, crushing and ultrasonic vibration screening are carried out to prepare molybdenum copper ultrafine composite powder to realize the atoms of molybdenum copper stage mix and evenly distributed.
The problems of component segregation and tissue holes are solved, and the high density and excellent thermoelectric comprehensive performance of molybdenum-copper alloy are achieved, which is suitable for industrial high-speed molding and pressing.
Smart Images

Figure CN119501053A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat sink materials, and in particular to a molybdenum-copper ultrafine composite powder and a preparation method thereof. Background Art
[0002] Heat sink materials are materials responsible for absorbing and quickly dissipating heat. In high-power packaging, ideal heat sink materials should have the following core characteristics: 1. High thermal conductivity: can effectively conduct heat and reduce temperature rise. 2. Low thermal expansion coefficient: avoid material deformation caused by temperature changes, affecting equipment performance. 3. High temperature stability: can maintain stable performance in high temperature environment. 4. Good processability: easy to process into various shapes and sizes to meet different application requirements. 5. Excellent physical and chemical stability: resist corrosion and oxidation and extend service life. Common heat sink materials include: 1. Tungsten copper alloy: has the low expansion characteristics of tungsten and the high thermal conductivity of copper, suitable for high-power device packaging and electronic packaging. 2. Molybdenum copper alloy: has the characteristics of both molybdenum and copper, with high thermal conductivity, low thermal expansion coefficient and non-magnetic characteristics. 3. Copper-molybdenum-copper-copper, i.e. CPC and copper-molybdenum-copper, i.e. CMC: has a low thermal expansion coefficient and excellent thermal conductivity, suitable for cooling high-power electronic components. Among them, molybdenum-copper alloy is a pseudo-alloy composite material formed by two immiscible metals. It combines the advantages of high hardness, high strength, and low thermal expansion coefficient of pure molybdenum and high thermal conductivity and high electrical conductivity of copper. Therefore, molybdenum-copper alloy is the most widely used electronic packaging heat sink material.
[0003] The molybdenum-copper alloy prepared by the existing technology is difficult to achieve mass production due to the difficulties of molybdenum and copper not being mutually soluble, poor wettability, and large melting point difference. First, the molybdenum-copper alloy is prepared by the melt infiltration method, and rolling is still required after melt infiltration to achieve a low expansion coefficient molybdenum-copper alloy. Therefore, it is not suitable for the preparation of small-sized molybdenum-copper alloys. Second, the liquid phase sintering method is usually used. The molybdenum-copper powder is usually mixed first. The mixed powder will cause the alloy to be difficult to densify due to the segregation of material components. Although mechanical alloying can be used to prepare a molybdenum-copper composite powder with fine particles dispersed and evenly distributed, the powder is severely agglomerated, and due to long-term ball milling, impurity elements such as iron will be introduced, which will weaken the thermal and electrical properties of the material. At the same time, the mechanical alloying method is difficult to achieve mass production. Summary of the invention
[0004] The present invention aims to solve the above-mentioned problems and provides a molybdenum-copper ultrafine composite powder and a preparation method to prepare the molybdenum-copper ultrafine composite powder and realize atomic-level mixing of molybdenum and copper; at the same time, it provides a preparation method that solves the problem of organizational segregation and realizes excellent thermal and electrical properties of molybdenum-copper alloys.
[0005] To achieve the above object, the present invention provides a molybdenum-copper ultrafine composite powder, which includes the following raw materials in parts by weight: 21.9-38.68 parts of copper nitrate, 30-40 parts of oxalic acid, and 100 parts of ammonium heptamolybdate.
[0006] Furthermore, the present invention also provides a method for preparing ultrafine molybdenum-copper composite powder, and the steps of the preparation method are as follows:
[0007] S1, liquid phase mixing; ammonium heptamolybdate and copper nitrate powder are mixed in a stoichiometric ratio, dissolved in deionized water, heated and stirred until the solution becomes transparent, and oxalic acid is added to obtain a mixed solution;
[0008] S2, atomizing; atomizing the mixed solution obtained in step S1 to obtain molybdenum-copper pre-alloyed molybdenum powder;
[0009] S3, reduction; the molybdenum-copper pre-alloyed molybdenum powder obtained in step S2 is loosened and then subjected to reduction heat treatment to obtain a molybdenum-copper powder after reduction;
[0010] S4, crushing and screening; the reduced molybdenum-copper powder obtained in step S3 is crushed and screened by a pulverizer to obtain a molybdenum-copper composite powder;
[0011] S5, pressing; using a servo press to press the molybdenum-copper composite powder obtained in step S4 into a molybdenum-copper blank at high speed using a steel die;
[0012] S6, high temperature liquid phase sintering; placing the molybdenum-copper blank of step S5 in a molybdenum wire sintering furnace, sintering at high temperature in a hydrogen atmosphere, and then keeping the temperature for a period of time, and then cooling to room temperature to obtain a molybdenum-copper ultrafine composite powder.
[0013] Furthermore, in step S1, the purity of the copper nitrate is not less than 99.95%, the purity of the ammonium heptamolybdate is not less than 99.95%, and the oxalic acid is analytically pure.
[0014] Furthermore, in step S2, the mixed solution is atomized, and the atomization method is water atomization; a high-pressure pump is used for pressurization, the atomization pressure is 40-120Mpa, the diameter of the guide tube is 2.0-10.0mm, and the guide tube is made of silicon dioxide. Nitrogen is used as the protective atmosphere, and the gas flow rate is 20-50L / min. The mixed solution passes through the middle and surrounds the guide tube at the bottom to form a liquid column flowing vertically downward. The pouring speed is 5-25kg / min. High-pressure water arranged around the liquid column breaks the liquid column into powder particles. The powder particles naturally fall into the cooling water for cooling, and then the water-containing powder is collected and vacuum filtered to obtain molybdenum-copper pre-alloyed molybdenum powder with a water content of 1-5wt%; the -170 mesh particle size content in the molybdenum-copper pre-alloyed molybdenum powder is not less than 95%.
[0015] Furthermore, in step S3, the molybdenum-copper pre-alloyed molybdenum powder is loosened, and the agglomeration diameter of the treated molybdenum-copper pre-alloyed molybdenum powder is less than 2 cm; then it is reduced, that is, the graphite boat containing the molybdenum-copper pre-alloyed molybdenum powder is placed in a hydrogen furnace, and reduced in steps, firstly, the temperature is raised to 200°C and kept warm for 60 minutes to fully volatilize the water; then the temperature is raised to 400°C and kept warm for 60 minutes to decompose and remove the organic matter; the temperature is continued to be raised to 500-650°C and kept warm for 60-90 minutes; then the temperature is raised to 800-950°C and kept warm for 120-360 minutes, and finally cooled with the furnace to obtain molybdenum-copper powder.
[0016] Furthermore, in step S4, the molybdenum-copper powder is crushed by a universal crusher, and then screened and separated by a sieve using a screening machine with an ultrasonic device, the sieve using a mesh size of 1000 to 10000, and the molybdenum-copper composite powder is obtained by screening and separation.
[0017] Furthermore, in step S5, the pressing pressure used by the servo press is 200-500 MPa, and the molybdenum-copper blank is obtained by high-speed pressing with a steel die.
[0018] Furthermore, in step S6, the molybdenum-copper blank is sintered at high temperature in a hydrogen atmosphere, and the purity of hydrogen is not less than 99.999%; the sintering temperature is first raised to 1100-1400°C, and kept at 1100-1400°C for 60-240 minutes, and then cooled to room temperature with the furnace to obtain a molybdenum-copper ultrafine composite powder.
[0019] Furthermore, in step S2, the mixed solution is atomized, and the atomization method can be gas atomization.
[0020] The beneficial effects of the present invention are as follows: 1. It solves the problems of component segregation, organizational pores, poor density, etc. in the preparation of molybdenum-copper alloys. The present invention prepares molybdenum-copper ultrafine composite powder by fully mixing the molybdenum-copper liquid phase, loosening the water-containing pre-alloyed molybdenum powder through gas atomization or water atomization treatment, hydrogen gradient thermal reduction, crushing, and ultrasonic vibration screening. The molybdenum-copper components of different proportions can be achieved by adjusting the ratio of powder raw materials, and the growth of copper phase can be suppressed during the sintering process of molybdenum-copper alloy, and the two phases of the sintered body are evenly distributed without agglomeration and segregation. Second, the present invention introduces the molybdenum-copper main phase in liquid form and stirs it under heating conditions to achieve atomic-level mixing of the two-phase elements, which solves the problems of insufficient mechanical alloying of molybdenum-copper mixed powder, long time consumption, and easy introduction of impurity elements, and solves the problem of weak mutual solubility of molybdenum and copper, and reduces the activation energy required for the diffusion of metal atoms in the molybdenum-copper alloy. Third, the present invention treats the molybdenum-copper mixed solution by atomization, which can effectively refine the pre-alloyed powder, make the material have low oxygen content, fine particle size and good powder sphericity, have a larger specific surface area and high surface energy, so that the molybdenum-copper ultrafine composite powder can provide higher driving force in the sintered state, help improve the organization, homogenize the composition, and finally obtain a molybdenum-copper material with high density and excellent comprehensive thermoelectric performance. 4. The present invention loosens the pre-alloyed molybdenum powder and performs hydrogen gradient thermal reduction to fully volatilize the residual moisture and impurities, and then obtains the molybdenum-copper ultrafine composite powder by crushing and ultrasonic screening. The powder has a particle size of less than 0.2um, a narrow particle size distribution, and good fluidity. The powder is suitable for industrial high-speed molding and pressing. After sintering, the structure is uniform and the density is high, that is, the relative density is above 99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the description are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 It is a flow chart of the preparation method of the invention.
[0023] The following is a further description of the implementation, functional features and advantages of the present invention with reference to the embodiments and accompanying drawings. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] It should be noted that, for directional words, such as the terms "center", "lateral", "longitudinal", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicating directions and positional relationships are based on the directions or positional relationships shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and cannot be understood as limiting the specific protection scope of the present invention. The terms "first", "second" and the like in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. The terms "including" and "having" in the specification and claims of the present application and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0026] Embodiment 1:
[0027] like Figure 1 As shown, the present invention provides a method for preparing ultrafine molybdenum-copper composite powder, and the preparation method comprises the following steps:
[0028] S1, liquid phase mixing; select copper nitrate, oxalic acid, and ammonium heptamolybdate in a weight ratio of 5:7:20; respectively mix ammonium heptamolybdate and copper nitrate powder, dissolve in deionized water, put into a reactor and heat, heat and stir until the solution becomes transparent, add oxalic acid, stir and react at 110°C for 4 hours to obtain a mixed solution; the purity of the copper nitrate is not less than 99.95%, the purity of the ammonium heptamolybdate is not less than 99.95%, and the oxalic acid is analytically pure; the ammonium heptamolybdate is (NH4)6Mo7O24·4H2O; the copper nitrate is Cu(NO)3·3H2O;
[0029] S2, atomization; the mixed solution obtained in step S1 is atomized to obtain molybdenum-copper pre-alloyed molybdenum powder; the mixed solution is atomized, and the atomization method is water atomization or gas atomization; a high-pressure pump is used for pressurization, the atomization pressure is 80Mpa, the diameter of the guide tube is 5mm, and the guide tube is made of silicon dioxide, nitrogen is used as the protective atmosphere, the gas flow rate is 30L / min, the mixed solution passes through the middle, surrounds the guide tube at the bottom to form a liquid column flowing vertically downward, the pouring speed is 10kg / min, and the high-pressure water arranged around the liquid column breaks the liquid column into powder particles, the powder particles naturally fall into the cooling water, are cooled, and then collected by an integrator to obtain a water-containing powder, vacuum filtered, and obtain a molybdenum-copper pre-alloyed powder with a water content of about 3wt%; the -170 mesh particle size content in the molybdenum-copper pre-alloyed molybdenum powder is not less than 95%;
[0030] S3, reduction; the molybdenum-copper pre-alloyed molybdenum powder obtained in step S2 is loosened, and the treated molybdenum-copper pre-alloyed molybdenum powder is ensured to have a powder agglomeration diameter less than 2 cm after loosening; then the molybdenum-copper pre-alloyed molybdenum powder is reduced by placing the graphite boat containing the molybdenum-copper pre-alloyed molybdenum powder into a hydrogen furnace, the hydrogen purity is not less than 99.95%, the hydrogen flow rate is 30L / min, and the reduction is carried out in steps, firstly the temperature is raised to 200°C, kept warm for 60min, so that the water is fully volatilized; then the temperature is raised to 400°C, kept warm for 60min, so that the organic matter is decomposed and removed; the temperature is continued to be raised to 600°C, kept warm for 60min; then the temperature is raised to 950°C, kept warm for 120min, and finally cooled with the furnace to obtain molybdenum-copper powder;
[0031] S4, crushing and screening; the reduced molybdenum-copper powder obtained in step S3 is crushed by a universal crusher, and then screened and separated by a sieve using a sieving machine with an ultrasonic device, the sieve using a 5000 mesh, and the obtained undersize is loaded into a mixing collector with a counter-rotating spiral device to obtain a molybdenum-copper composite powder; the diameter of the molybdenum-copper composite powder particles is not greater than 0.2um, and the powder particle morphology is spherical when observed by scanning electron microscopy.
[0032] S5, pressing; the molybdenum-copper composite powder obtained in step S4 is pressed into a molybdenum-copper blank at a high speed using a servo press with a pressing pressure of 400 MPa using a steel die; the molybdenum-copper blank, i.e., Mo70Cu30 green blank, is obtained with a molding pressure of 500 MPa.
[0033] S6, high temperature liquid phase sintering; placing the molybdenum-copper blank of step S5 in a molybdenum wire sintering furnace, and performing high temperature sintering in a hydrogen atmosphere, wherein the purity of the hydrogen is not less than 99.999%; firstly raising the sintering temperature to 1300°C, and maintaining it at 1100-1400°C for 120 minutes, and then cooling it naturally with the furnace to obtain a molybdenum-copper ultrafine composite powder, i.e., Mo70Cu30 composite material.
[0034] The beneficial effect of the first embodiment is that: according to the above method, a molybdenum-copper ultrafine composite powder, namely Mo70Cu30 material, is obtained. The mass density of the tested sample is 9.8g / cm 3 , density 99%, average linear thermal expansion coefficient of 6.82ppm / K from room temperature to 400℃, thermal conductivity of 195W / (m·k).
[0035] The other embodiments differ from the first embodiment in that the amounts of raw materials used are different, or the raw materials are replaced among the multiple available ones specified in this case, or the various data in the preparation process are different, which are not listed here one by one.
[0036] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents, and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A molybdenum-copper ultrafine composite powder, characterized in that: The molybdenum-copper ultrafine composite powder comprises the following raw materials in parts by weight: 21.9-38.68 parts of copper nitrate, 30-40 parts of oxalic acid, and 100 parts of ammonium heptamolybdate.
2. The method for preparing a molybdenum-copper ultrafine composite powder according to claim 1, characterized in that: The preparation method steps are as follows: S1, liquid phase mixing; ammonium heptamolybdate and copper nitrate powder are mixed in a stoichiometric ratio, dissolved in deionized water, heated and stirred until the solution becomes transparent, and oxalic acid is added to obtain a mixed solution; S2, atomizing; atomizing the mixed solution obtained in step S1 to obtain molybdenum-copper pre-alloyed molybdenum powder; S3, restore; The molybdenum-copper pre-alloyed molybdenum powder obtained in step S2 is loosened and then subjected to reduction heat treatment to obtain molybdenum-copper powder after reduction; S4, crushing and screening; the reduced molybdenum-copper powder obtained in step S3 is crushed and screened by a pulverizer to obtain a molybdenum-copper composite powder; S5, pressing; using a servo press to press the molybdenum-copper composite powder obtained in step S4 into a molybdenum-copper blank at high speed using a steel die; S6, high temperature liquid phase sintering; placing the molybdenum-copper blank of step S5 in a molybdenum wire sintering furnace, sintering at high temperature in a hydrogen atmosphere, and then keeping the temperature for a period of time, and then cooling to room temperature to obtain a molybdenum-copper ultrafine composite powder.
3. The method for preparing a molybdenum-copper ultrafine composite powder according to claim 2, characterized in that: In step S1, the purity of the copper nitrate is not less than 99.95%, the purity of the ammonium heptamolybdate is not less than 99.95%, and the oxalic acid is analytically pure.
4. The method for preparing a molybdenum-copper ultrafine composite powder according to claim 3, characterized in that: In step S2, the mixed solution is atomized, and the atomization method is water atomization; a high-pressure pump is used for pressurization, the atomization pressure is 40-120Mpa, the diameter of the guide tube is 2.0-10.0mm, and the guide tube is made of silicon dioxide. Nitrogen is used as the protective atmosphere, and the gas flow rate is 20-50L / min. The mixed solution passes through the middle and surrounds the guide tube at the bottom to form a liquid column flowing vertically downward. The pouring speed is 5-25kg / min. High-pressure water arranged around the liquid column breaks the liquid column into powder particles. The powder particles naturally fall into the cooling water for cooling, and then the water-containing powder is collected and vacuum filtered to obtain molybdenum-copper pre-alloyed molybdenum powder with a water content of 1-5wt%; the -170 mesh particle size content in the molybdenum-copper pre-alloyed molybdenum powder is not less than 95%.
5. The method for preparing a molybdenum-copper ultrafine composite powder according to claim 4, characterized in that: In step S3, the molybdenum-copper pre-alloyed molybdenum powder is loosened, and the agglomeration diameter of the molybdenum-copper pre-alloyed molybdenum powder after the treatment is less than 2 cm; then it is reduced, that is, the graphite boat containing the molybdenum-copper pre-alloyed molybdenum powder is placed in a hydrogen furnace, and reduced in steps, firstly, the temperature is raised to 200° C. and kept warm for 60 minutes to fully volatilize the water; then the temperature is raised to 400° C. and kept warm for 60 minutes to decompose and remove the organic matter; Continue to heat up to 500-650°C and keep warm for 60-90 minutes; then heat up to 800-950°C and keep warm for 120-360 minutes, and finally cool with the furnace to obtain molybdenum-copper powder.
6. The method for preparing a molybdenum-copper ultrafine composite powder according to claim 5, characterized in that: In step S4, the molybdenum-copper powder is crushed by a universal crusher, and then screened and separated by a sieve using a screening machine with an ultrasonic device, the sieve using a mesh size of 1000 to 10000, and the molybdenum-copper composite powder is obtained by screening and separation.
7. The method for preparing a molybdenum-copper ultrafine composite powder according to claim 6, characterized in that: In step S5, the pressing pressure used by the servo press is 200-500 MPa, and the molybdenum-copper blank is obtained by high-speed pressing through a steel die.
8. The method for preparing a molybdenum-copper ultrafine composite powder according to claim 7, characterized in that: In step S6, the molybdenum-copper blank is sintered at high temperature in a hydrogen atmosphere, and the purity of hydrogen is not less than 99.999%. The sintering temperature is first raised to 1100-1400°C, and kept at 1100-1400°C for 60-240 minutes, and then cooled to room temperature with the furnace to obtain molybdenum-copper ultrafine composite powder.
9. The method for preparing a molybdenum-copper ultrafine composite powder according to claim 4, characterized in that: In step S2, the mixed solution is atomized, and the atomization method can be gas atomization.